The Role of Cash Waqf in Financing Renewable Energy Projects for Sustainable Islamic Economic Development - Lies Anggi Puspita Dewi; Agus Purnomo; Tomas G. Belano (Green Economics: International Journal of Islamic and Economic Education, 2024)
This study examines the significant role of cash waqf in financing renewable energy projects for sustainable Islamic economic development. Using a descriptive qualitative approach, the research collects data through case analysis of Islamic social finance institutions involved in renewable energy funding, along with interviews with key informants such as waqf managers and Islamic finance practitioners. The data were analyzed using thematic analysis to identify recurring patterns and key themes related to cash waqf’s application in renewable energy projects. The findings show that cash waqf offers a more sustainable funding model compared to conventional charity. By preserving the principal and only utilizing the income, cash waqf provides long-term resources for clean energy projects. The study also highlights cash waqf’s advantages in terms of accountability and transparency, as waqf institutions are required to provide auditable financial reports. In contrast, conventional charity is often short-term and lacks structured oversight, making cash waqf a more efficient model for financing ongoing projects like renewable energy. The research also identifies challenges in implementing cash waqf, such as regulatory issues and lack of awareness. However, there are significant opportunities to address these challenges through collaborations with Islamic banks and sustainable financial institutions. This study proposes integrating cash waqf with Islamic finance principles and ESG criteria to increase its impact on renewable energy projects. With appropriate regulation and increased awareness, cash waqf can play a crucial role in driving the transition to a sustainable green economy.